Impact of family income on the development of gestational diabetes mellitus and the associated birth outcomes: A nationwide study - Fu‐Shun Yen; James Cheng‐Chung Wei; Yi‐Ling Wu; Yu‐Ru Lo; Chih‐Ming Chen; Chii‐Min Hwu; Chih‐Cheng Hsu (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction The relationship between economic disadvantages and the risk of developing gestational diabetes mellitus (GDM), as well as its impact on birth outcomes, remains uncertain. Materials and Methods From the Taiwan Maternal and Child Health Database, we identified 984,712 pregnant women between 1 January 2007 and 31 December 2018. Using propensity score matching, we selected 5,068 pairs of women across four income levels: very low, low, middle and high. We used a multivariable Cox regression model to assess the risk of GDM in these pregnant women and analyzed the birth outcomes. Results The mean age of the pregnant women was 30.89 years. We found no significant difference in GDM risk among pregnant women with different family income. However, newborns of women with GDM and very low‐income were at higher risk for several adverse conditions, such as small for gestational age (adjusted odds ratio (aOR) 1.17, 95% confidence interval (CI) 1.04–1.31), large for gestational age (aOR 1.27, 95% CI 1.08–1.51), hypoxic–ischemic encephalopathy (aOR 3.19, 95% CI 1.15–8.86), respiratory distress (aOR 1.58, 95% CI 1.14–2. 19), congenital anomalies (aOR 1.32, 95% CI 1.08–1.62), jaundice requiring phototherapy or exchange transfusion (aOR 1.14, 95% CI 1.05–1.24) and so on. Conclusions This study found that low family income alone was not associated with GDM development. However, for a GDM pregnancy, pregnant women with lower income had worse birth outcomes. Improving maternal health and nutrition among low‐income pregnant women with GDM might be critical to improving birth outcomes.